NASKAH TASAWUF TEUNGKU KHATIB LANGGIEN: Sebuah Kajian Kodikologis - - Fakhriati (Widyariset, 2010)
The manuscript of Teungku Khatib Langgien that can be included in tasawuf category is one of cultural heritages for this nation. This must be taken into account since there are two undeniable reasons emerge. First, the condition of this manuscript is in bad condition and will be disappeared in a short time. Second, writing tradition of this manuscript becomes difficult to read while its contents provide absolutely valuable information and knowledge for the readers. Therefore, one of the ways to keep this cultural heritage is by performing research on codicological perspective. The purpose of this research is to reveal all information related to history and physics of the manuscript. This research is qualitative by using descriptive analysis. The method using in this research are collectingdata through inventarisation, analyzing, and interpreting data. There are, at least, two inventions had been found in this research. First, based on the paper used in this manuscripts and its colophon, the manuscript was produced and written in 19th century. Second, European papers and ink used for a manuscript can effect the condition of the manuscript become worst. Thus, to keep alive of such this manuscript needs special conservation.